An Empirical Evaluation of the Discounted Cash Flow Model and Residual Income Model in Equity Valuation - Jadallah, Saleem (2011)
The collapse of the world markets hinted at the significant overestimation of assets on the market. Assets have been mismanaged and severe losses have been incurred. There has since been renewed interest in fundamental valuation models as they are believed to capture a more complete view of firm value. In this paper, we follow up on this renewed interest by empirically analysing the performance and explanatory power of two major present value models, the Discounted Cash Flow model (DCF) and the Residual Income Model (RIM), and in the process, concluding which model works best in the valuation of equity.